Pattern of Haematological Disorders in a Tertiary Diabetic Hospital: A Pilot Study (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Background: Patients with diabetes mellitus may suffer from various haematological diseases. A one year prospective study from July 2007 to July 2008 was done in the Department of Transfusion Medicine of BIRDEM to see the distribution of haematological diseases among the referred patients. Objective: The aim of the study was to observe the pattern of hematological diseases in patients with diabetes mellitus. Materials and Method: A total number of 111 new cases suffering from various haematological disorders were included in this observational study for one year duration from July 2007 to July 2008. Patients were diagnosed by peripheral blood film, complete blood count, bone marrow, hemoglobin electrophoresis. History of the patients including clinical informations were recorded with written consent from their very first arrival. Results: Among the studied 111 patients, 23 (20.72 %) were suffering from various types of haemoglobinopathies and 88 (79.28 %) with other haematological diseases. When glycemic status was considered 65 (58.56%) patients out of 111 showed diabetes mellitus along with haematological diseases. Among those diabetic patients 11% had haemoglobinopathies, 25% had bleeding disorders, autoimmune diseases and marrow aplasia, 27% suffered from deficiency anaemia, anaemia of chronic diseases and haemochromatosis , where as 37% had various clonal haematological malignancy. Among haemoglobinopathies group, beta thalassaemia major was 21.74%, beta thalassaemia trait 47.83%, haemoglobin Etrait 17.39% and haemoglobin E-disease was 13.04%. Out of 23 Haemoglobinopathy patients 14 (60.87%) were male and 9 (39.13%) were female. Out of 88 patients with other haematological diseases except haemoglobinopathy 26 (29.54%) were of various haematological malignancies, 16 (18.18%) were of bleeding disorders, autoimmune diseases and marrow aplasia and 47 (53.41%) out of 88 patients had deficiency anaemia, anaemia of chronic diseases and haemochromatosis. In this group 40 patients (45%) were male and 48 (55%) patients were female. Conclusion: This study shows majority patients with haematological diseases were suffering from diabetes mellitus. Among the haemoglobinopathies group, male were predominant and among the other haematological diseases except haemoglobinopathies group, female were predominant. From this study we suggest further multicentred study to see any precipitating cause between haematological diseases and diabetes mellitus. There is also an immense need to maintain registry of haematological diseases with a plan to establish state of art haematology services in all tertiary specialized hospitals including BIRDEM. Key words: haemoglobinopathy, clonal hematological malignancies, anaemia, bleeding disorder, diabetes mellitus, cancer DOI:10.3329/jbcps.v27i3.4292 J Bangladesh Coll Phys Surg 2009; 27: 148-154